2014
DOI: 10.1177/0954406214537806
|View full text |Cite
|
Sign up to set email alerts
|

Design of an induction heating coil coupled with magnetic flux concentrators for barrel heating of an injection molding machine

Abstract: In an injection molding machine, the conventional barrel heating system which uses resistance heating method (RH) has some drawbacks such as low heating rate, long heating time, and energy loss. With induction heating (IH) technique, the barrel can better handle almost all of these disadvantages. However, non-uniform temperature distribution on inside surface of a barrel is the main drawback of induction heaters. A working coil coupled with magnetic flux concentrators via adjustment of magnetic flux concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…µ MFC is the magnetic permeability of the heated material, ρ is the charge density. Through the further derivation, the electro-magnetic equations in the isotropic dielectric material in this planar moving induction heating are governed by the Equations (5) and (6) [2,10].…”
Section: Analytical Modeling Of the Temperature Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…µ MFC is the magnetic permeability of the heated material, ρ is the charge density. Through the further derivation, the electro-magnetic equations in the isotropic dielectric material in this planar moving induction heating are governed by the Equations (5) and (6) [2,10].…”
Section: Analytical Modeling Of the Temperature Calculationmentioning
confidence: 99%
“…Since the electromagnetic field distribution inside the spiral coil is relatively uniform, the induction heating has the characteristics of fast heating and high efficiency [2]. However, the coil required for the planar induction heating is significantly different from the traditional spiral coils, in which the magnetic field distribution is difficult to effectively concentrated, the air impedance of the system loop is too large and the heating temperature is not uniform and difficult to control accurately [5][6][7]. The efficiency of the planar induction heating extensively depends on the effective conversion of the electromagnetic field of the coil and the reasonable matching of the In recent years, in order to apply the induction heating process more effectively, many scholars have conducted more research on induction heating [11][12][13][14][15][16][17][18][19], including numerical modeling of induction heating process and electromagnetic field conversion mechanism analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, it is impossible to deduce the electromagnetic and temperature distribution analytically. Therefore, finite element method (FEM)-based numerical simulation has become a popular mean used by many researchers to analyze the induction heating process in industrial applications, including metal forming, 613 melting 14 and molding, 15 crystal growing, 16 wafer packaging, 17,18 and welding process. 19,20 Cho 6 established a cost-effective coupled electromagnetic-thermal model to numerically analyze the solutions of both stationary and moving workpiece under low frequency induction heating system, which could predict more precise results of temperature distribution in the variable magnetic field than the previous model.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the uniform temperature distribution can be achieved by optimizing the arrangement of the magnetizer. 16,17 However, the design cost will be greatly increased, and it is hard to flexibly adjust the temperature distribution in according to the arrangement of the magnetizer. Nian et al found that the temperature uniformity in the electromagnetic heating process can be improved by increasing the thickness of the mold 18 but may prolong the heating time and increase the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the uniform temperature distribution can be achieved by optimizing the arrangement of the magnetizer. 16,17 However, the design cost will be greatly increased, and it is hard to flexibly adjust the temperature distribution in according to the arrangement of the magnetizer. Nian et al.…”
Section: Introductionmentioning
confidence: 99%